Scorpion Venom Polypeptide Inhibits Pulmonary Epithelial-Mesenchymal Transition in Systemic Sclerosis-Interstitial Lung Disease Model Mice by Intervening TGF-β1/Smad Signaling Pathway. (13th April 2022) - Zhang, Yan; Xu, Liping; Chen, Qiang; Guan, Tianrong; Lin, Na; Xu, Danyang; Lu, Lihong; Dai, Qiaoding; Song, Xinwei
Abstract : Objective . Interstitial lung disease (ILD) is an important complication of systemic sclerosis (SSc). The aim of this study was to investigate the effect and possible mechanism of polypeptide extract of scorpion venom (PESV) on SSc-ILD. Methods . C57/BL6 mice were injected with bleomycin to establish a SSc-ILD model. Different concentrations of PESV solution were administered to SSc-ILD mice, and dexamethasone was used as a positive control. H&E staining and Masson staining were used to observe the pathological changes. The TGF- β 1 expression level was detected by immunohistochemistry. The expression of epithelial-mesenchymal transition (EMT)-related proteins was detected by Western blot, and the expression of TGF- β 1/Smad pathway-related proteins was also detected. The content of inflammatory cytokines in serum and BALF was determined by ELISA. Results . Pathological analysis showed that PESV could alleviate SSc-ILD-induced pulmonary inflammation and fibrosis. Compared with the model group, the content of inflammatory cytokines IL-6 and TNF- α significantly decreased after PESV treatment. PESV could increase the expression of epithelial marker (E-cadherin) and reduce the expression of interstitial markers (collagen I, vimentin, N-cadherin, and a-SMA). In addition, PESV could reduce the expression level of TGF- β 1/Smad pathway-related protein. Conclusion . PESV can attenuate SSc-ILD by regulating EMT, and the effect was linked to the TGF- β 1/Smad signaling pathway, which indicated that PESV may serve as a candidate drug for SSc-ILD.